CRECIMIENTO Y CARACTERÍSTICAS FERMENTATIVAS DE Kluyveromyces marxianus EN MATRICES DERIVADAS DE LACTOSUERO (FAVE Sección Ciencias Veterinarias, 2021)
Milk whey has a high content of organic matter; therefore, uncontrolled discharge can cause environmental problems. An alternative for whey utilization is the production of fermented alcoholic beverages by means of the yeast Kluyveromyces marxianus, able to use lactose as a carbon source. Four different liquid growth media were prepared: whey powder (SP) and demineralized whey powder (SPD) (65 g/L) dissolved in sterilized distilled water; SPCal, similar to SP in composition, but sterilized and centrifuged to remove proteins, and milk permeate (PER). All media were fermented by 24 hours at 30°C. Samples were taken every 8 hours, for pH, biomass, ethanol and lactose determination. K. marxianus (LFIQK1 strain) growth was similar in SP, SPD and SP Cal (biomass between 2 – 3 g/L) and lower in PER. Moderate pH decline was observed, final values being between 4,7 and 5,4. Significant lactose consumption was observed in every growth media, with final values around 12 g/L and good ethanol production, especially for SP, SPD, and PER mediums (17,0±0,7; 17,6±0,5; 16,3±0,2 g/L respectively). These results are encouraging for the production of alcoholic beverages from the studied media using K. marxianus as the fermentation agent.